Functional activity and chromatin configuration of SV40 enhancer injected in Xenopus laevis oocytes. - Spinelli, G (1985)
The SV40 enhancer microinjected into the nuclei of X. laevis oocytes is able to activate transcription about 100-fold when cloned upstream of the SV40 early promoter region or about 10-fold regardless of its orientation when located at a long distance from a test gene (bacterial chloramphenicol acetyl transferase). This effect is qualitatively and quantitatively similar to that observed when analogous constructions were transfected into mammalian cells. Making use of a direct labelling technique for the analysis of the chromatin structure we could show that the SV40 enhancer region in the microinjected plasmids is particularly accessible to cleavage with MNase or DNAse I. Single sites in the 72 bp repeats have been mapped at the nucleotide level.